Teflon granulomas mimicking cerebellopontine angle tumors following microvascular decompression. (19th June 2016) - Deep, Nicholas L.; Graffeo, Christopher S.; Copeland, William R.; Link, Michael J.; Atkinson, John L.; Neff, Brian A.; Raghunathan, Aditya; Carlson, Matthew L.
Abstract : Objectives/Hypothesis: To report two patients with a history of microvascular decompression (MVD) for hemifacial spasm who presented with Teflon granulomas (TG) mimicking cerebellopontine angle (CPA) tumors and to perform a systematic review of the English‐language literature. Study Design: Case series at a single tertiary academic referral center and systematic review. Methods: Retrospective chart review with analysis of clinical, radiological, and histopathological findings. Systematic review using PubMed, Embase, MEDLINE, and Web of Science databases. Results: Two patients with large skull base TGs mimicking CPA tumors clinically and radiographically were managed at the authors' institution. The first presented 4 years after MVD with asymmetrical sensorineural hearing loss, multiple progressive cranial neuropathies, and brainstem edema due to a growing TG. Reoperation with resection of the granuloma confirmed a foreign‐body reaction consisting of multinucleated giant cells containing intracytoplasmic Teflon particles. The second patient presented 11 years after MVD with asymmetrical sensorineural hearing loss and recurrent hemifacial spasm. No growth was noted over 2 years, and the patient has been managed expectantly. Only one prior case of TG after MVD for hemifacial spasm has been reported in the English literature. Conclusions: TG is a rare complication of MVD for hemifacial spasm. The diagnosis should be suspected in patients presenting with a new‐onset enhancing mass of the CPA after MVD, even when performed decades earlier. A thorough clinical and surgical history is critical toward establishing an accurate diagnosis to guide management and prevent unnecessary morbidity. Surgical intervention is not required unless progressive neurologic complications ensue. Level of Evidence: 4 Laryngoscope, 127:715–719, 2017